Population structure of Clinostomum complanatum (Trematoda: Digenea) with new data on haplotype diversity of flukes from Slovakia and Italy - Juhásová Ľudmila; Bazsalovicsová Eva Čisovská; Caffara Monica; Radačovská Alžbeta; Gustinelli Andrea; Dinisová Lucia; Syrota Yaroslav; Králová-Hromadová Ivica (Parasite)
The fluke Clinostomum complanatum, a parasite of piscivorous birds, but also reptiles and rarely mammals, has established several foci in the western Palaearctic regions. Previous studies pointed out the complicated taxonomy of the genus, but broader population genetic analysis of C. complanatum has not yet been carried out. The aim of this study was to determine the structure, intraspecific variability, and diversity of mitochondrial cox1 haplotypes of C. complanatum from different localities in Slovakia (Danube floodplain forests) and Italy (Emilia-Romagna and Tuscany), as well as to evaluate the interrelationships among populations from Europe, the Middle East, and North Africa. The genetic structure of C. complanatum from Slovakia and Italy was represented by a great number of haplotypes, showing stable populations with high intraspecific diversity. The haplotypes of samples from other localities (Romania, Turkey, Egypt, and Iran) showed possible gene flow among the populations from Central Europe down to the Mediterranean region, North Africa, and the Middle East. The genetic homogeneity of these samples can be linked to the distribution and migratory routes of the definitive hosts, aquatic piscivorous birds, mainly herons and cormorants, that spread parasite eggs among the continents.